Regionale StadtLandschaften – Muster der lebensweltlichen Erfahrung postindustrieller Raumproduktion zwischen Homogenisierung und Fragmentierung - Kropp, Cordula (Raumforschung und Raumordnung | Spatial Research and Planning, 2015)
Customarily, cities are being described in terms of their historical origins and as manifestations of political conceptions, while rural areas are being characterized by natural spatial features and their contrast to cities. Due to its hybridity, “regional rurbanism” defies categorical con- sideration. It is more likely perceived as the result of the ambiguous interaction of social and natural, planned and unplanned, endogenous and exogenous forces. When it comes to living and working in these spatial contexts labels such as “rural” or “urban” have less and less value. What does the hybridization mean for everyday spatial experi- ences? Henri Lefebvre, whose spatial triad concepts are a starting point for the considerations at hand, discarded the urban-rural-differentiation on the grounds that it no lon- ger corresponded to the social production of space under the terms of global urbanization processes and world-wide capitalism. And yet, along with tendencies toward homog- enization, there are fragmentation processes at work, which accentuate spatial inequalities and received the attention in a two-dimensional treatment of spatial dynamics. The pa- per uses the above-mentioned, common characteristics of post-industrial spatial production as a starting point for the reconstruction of four spatial trends – homogenization, po-larization, fragmentation and diversification. It is discussed how they may shape regionally varying spatial experiences of the life-world in order to better understand the constel- lationofconditionsthatapplytocivicspaceappropriation beyond the classifications of planning. The study opens up novel perspectives for basic research in the fields of ur- ban and regional planning that leave growth policy criteria behind.
Keywords: Social production of space; Spatial experience; Rurbanisation; Homogenization; Fragmentation